Universal vortex formation time of flapping flight - Yukun Sun; Emily Palmer; Christopher Dougherty; Cade Sbrocco; Aspen Shih; Jena Shields; Chris Roh (Proceedings of the National Academy of Sciences, 2025)
Biological flyers periodically flap their appendages to generate aerodynamic forces. Extensive studies have made significant progress in explaining the physics behind their propulsion in cruising by developing scaling laws of their flight kinematics. Notably Strouhal number ( St ; ratio of flapping frequency times stroke amplitude to cruising speed) has been found to fall in a narrow range for animal cruising flights. However, St exhibits strong correlation to flight conditions; as such, its universality has been confined to preferred flight conditions. Since the leading-edge vortices (LEV) on flapping appendages generate the majority of propulsive forces, here we take the perspective of LEV circulation maximization, which generalizes the dimensionless vortex formation time to flapping flight. The generalized vortex formation time scales the duration of vorticity injection with the rate of total vorticity growth inside the LEV and the maximum vorticity allowed inside it. By comparing the new scaling with St of previously reported animal cruising flights of 28 species, we show that the generalized vortex formation time is consistent across different animals and cruising locomotion, independent of flight conditions. This finding advances the fundamental principles underlying the complex wing kinematics of biological flyers and highlights a unifying framework for understanding biolocomotion.